PENGEMBANGAN METODE PEMBELAJARAN GALLERY WALK UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK PADA PELAJARAN IPS - Tasya Nor Intan Pratiwi; Ni'matuz Zuhroh (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2022)
The importance of creativity in social studies learning activities is to determine changes in behavior, knowledge, and skills in solving social problems that can be applied. This encourages researchers to develop the Gallery Walk learning method that can increase the creativity of students through the Social Sciences learning curriculum for class VII MTS Shirothul Fuqoha'. The purpose of this study is to (1) explain the planning for the development of the Gallery Walk learning method in increasing the creativity of students in social studies subjects for MTS Shirothul Fuqoha' Malang students. (2) Explaining the implementation of the Gallery Walk learning method in increasing students' creativity in social studies subjects for MTS Shirothul Fuqoha' Malang students, (3) Explaining the results of implementing the Gallery Walk learning method in increasing students' creativity in social studies subjects for MTS Shirothul Fuqoha' Malang students. The research method in this thesis uses the R&D (Research and Development) research method with the ADDIE development model. The measurement of validity of the development results was measured using an assessment questionnaire by validators of method experts, material experts, social studies teachers, and students of class VII B as the experimental class and class VII C as the control class. The results of the study are as follows: (1) there are 5 development processes, namely: Analysis, Design, Development, Implement, and Evaluate. (2) Product assessment through questionnaires got scores: 90% method expert, material expert 78%, social studies teacher 92%. All of these values ​​are stated as “No Revision Needed”. (3) The results of the calculation of the Paired Samples Test obtained a significance value (2-tailed) of 0.000. Because 0.000 < 0.05 then H0 is rejected and H1 is accepted. So it can be concluded that the Gallery Walk learning method can increase the creativity of students. Abstrak Pentingnya kreativitas dalam kegiatan pembelajaran IPS yaitu untuk mengetahui perubahan tingkah laku, pengetahuan, maupun keterampilan dalam memecahkan masalah sosial dan dapat diterapkan. Hal tersebut mendorong peneliti untuk mengembangkan metode pembelajaran Gallery Walk yang dapat meningkatkan kreativitas peserta didik yang sesuai dengan kurikulum pembelajaran IPS untuk kelas VII MTS Shirothul Fuqoha’. Tujuan penelitian ini adalah untuk (1) Menjelaskan perencanaan pengembangan metode pembelajaran Gallery Walk dalam meningkatkan kreativitas peserta didik pada mata pelajaran IPS siswa MTS Shirothul Fuqoha’ Malang. (2) Menjelaskan implementasi metode pembelajaran Gallery Walk dalam meningkatkan kreativitas peserta didik pada mata pelajaran IPS siswa MTS Shirothul Fuqoha’ Malang, (3) Menjelaskan hasil implementasi metode pembelajaran Gallery Walk dalam meningkatkan kreativitas peserta didik pada mata pelajaran IPS siswa MTS Shirothul Fuqoha’ Malang. Metode penelitian dalam skripsi ini menggunakan metode penelitian R&D (Research and Development) dengan model pengembangan ADDIE. Pengukuran validitas hasil pengembangan diukur menggunakan angket penilaian oleh validator ahli metode, ahli materi, guru IPS, siswa kelas VII B sebagai kelas eksperimen dan kelas VII C sebagai kelas kontrol. Hasil penelitian adalah sebagai berikut: (1) terdapat 5 proses pengembangan yaitu: Analysis, Design, Development, Implement, Evaluate. (2) Penilaian produk melalui angket mendapatkan nilai: ahli metode 90%, ahli materi 78%, guru IPS 92%. Seluruh nilai ini dinyatakan “Tidak Perlu Revisi”. (3) Hasil perhitungan Uji Paired Samples Test diperoleh nilai signifikasi (2-tailed ) sebesar 0,000. Karena 0,000 < 0,05 maka H0 ditolak dan H1 diterima. Maka dapat disimpulkan metode pembelajaran Gallery Walk dapat meningkatakan kreativitas peserta didik.